Nightmares and hallucinations with aprepitant and opium powder: a suspected drug–drug interaction. Issue 2 (26th November 2018) - Narjoux, Grégoire; Clarenne, Justine; Azzouz, Brahim; Zeller, Pauline‐Saraï; Slimano, Florian; Bouché, Olivier
Abstract: Polypharmacy of elderly oncology patients and fragmented medication management are well‐known risk factors for drug–drug interactions (DDIs). These interactions can occur among antineoplastic, ongoing chronic treatment(s) and chemotherapy‐associated treatments, like antiemetics. Clinically relevant interactions based on enzyme‐ or transporter‐inhibition phenomena of active drugs can increase the frequency of their DDIs. We describe a strongly suspected elderly cancer patient's DDI between aprepitant and opium powder in the context of an irinotecan‐based regimen manifested by nightmares and visual hallucinations. We discuss this DDI's hypothetical pharmacological mechanisms and management.